COMPARISON OF THREE PROGRAMMABLE FREEZING PROTOCOLS FOR THE CRYOPRESERVATION OF BUFFALO BULL SEMEN - DALAL, J; KUMAR, A; HONPARKHE, M; SINGHAL, S; SINGH, N (The Indian Journal of Animal Reproduction, 2016)
Twenty-one ejaculates from three Murrah buffalo bulls (7 ejaculates per bull) were frozen according to three different freezing protocols using a bio-freezer. Post thaw semen samples were evaluated and the average percentage of individual motility, progressive motility, viability, sperm membrane integrity and total sperm abnormalities was similar (p>0.05) in three protocols.
Keywords: Buffalo bull; Cryopreservation; Freezing rate; Programmable freezing; Semen